The 'museumification' of the Scottish soldier and the meaning-making of Britain's wars. Issue 3 (2nd July 2020) - Danilova, Nataliya; Purnell, Kandida
ABSTRACT: Drawing on interviews with curators of Scotland's military museums and fieldwork ethnographies, this article explores how the Scottish Soldier is enacted through curation and how, through artefacts and stories, curators (re)produce the Scottish Soldier within and through their museums' spaces. This article identifies three intertwining curatorial practices: (a) Production of a Scottish warrior 'dreamscape' through a dual technique of displaying symbolic representations of Scots-as-warriors while simultaneously reframing the controversies of Scotland's contribution to British colonial wars and recent conflicts; (b) Construction of classed, raced, and gendered hierarchies through the curation of war-informing artefacts (uniforms, medals, and weaponry) – all of which sustain the dominance of warrior-like masculinity deployed in the service of the British state; and (c) Humanization of soldiers via the disruption of stereotypical warrior codes and the making visible of personalized and locally based war stories working towards decontextualisation and sentimentalization of war. We argue that these curatorial practices enable the reproduction of a sacrificial Scottish Soldier and through this process they assist in the normalization of Britain's wars.